The Quality of Interactions Schedule (QuIS) and person-centred care: Concurrent validity in acute hospital settings - Jackie Bridges; Lisa Gould; Joanna Hope; Lisette Schoonhoven; Peter Griffiths (Elsevier, 2019)
Background: There is a lack of consensus on how the practices of health care workers may be assessed and measured in relation to compassion. The Quality of Interactions Schedule (QuIS) is a promising measure that uses independent observers to assess the quality of social interactions between staff and patients in a healthcare context. Further understanding of the relationship between QuIS and constructs such as person-centred care would be helpful to guide its future use in health research. Objective: This study aimed to assess the validity of QuIS in relation to person-centred care measured using the CARES® Observational Tool (COT™). Methods: 168 nursing staff-patient care interactions on adult inpatient units in two acute care UK National Health Service hospitals were observed and rated using QuIS and COT™. Analyses explored the relationship between summary and individual item COT™ scores and the likelihood of a negative (lower quality) QuIS rating. Results: As the degree of person-centred care improved, QuIS negative ratings generally decreased and positive social ratings increased. QuIS-rated negative interactions were associated with an absence of some behaviours, in particular staff approaching patients from the front (relative risk (RR) 3.7), introducing themselves (RR 3.1), smiling and making eye contact (RR 3.4), and involving patients in their care (RR 3.7). Conclusion: These findings provide further information about the validity of QuIS measurements in healthcare contexts, and the extent to which it can be used to reflect the quality of relational care even for people who are unable to self-report.